Synchrotron X-ray imaging study on the mechanism of solids transfer to bitumen froth during oil sands flotation 1: True flotation - Hanyu Zhang; Liuyin Xia; Ning Zhu; Sergey Gasilov; Iris He; Xiaofan Ding (Cleaner Engineering and Technology)
Unwanted mineral solids in bitumen froth can lead to increased solvent usage and higher hydrocarbon loss in downstream processing, negatively impacting the cost-effectiveness and sustainability of synthetic crude oil production. Enhancing the quality of bitumen froth with fewer solids is a goal for oil sands processors. This study presents an in-situ analysis of the particle size distribution and association of solids in bitumen froth, thereby uncovering solids transport mechanisms, such as true flotation. Oil sands flotation experiments were conducted with 30% pulp density, at 50 °C and pH 8.5. The collected bitumen froth was immediately characterized using synchrotron-based X-ray imaging by a monochromatic X-ray with photon energy of 60 keV provided by 05ID-2 beamline of the BioMedical Imaging and Therapy (BMIT) facility at the Canadian Light Source (CLS). This characterization method can finish a typical CT scan with 2000 projections in less than 3 min, and thus allows for in-situ imaging of freshly prepared bitumen froth without the need for special arrangements, such as freezing. 14, 234 unwanted solids carried over into bitumen froth were visualized, 98.9 wt% of them were sand particles, which is consistent with mineral liberation analysis (MLA) results. This study introduced an innovative image segmentation technique to quantify the transfer of particles into the bitumen froth via true flotation. Statistical analysis revealed that approximately 53 wt% of sand particles were collected due to true flotation. Furthermore, the median particle size (P50) for sand particles entering froth by true flotation was determined to be 67.6 μm, significantly larger than the 30.6 μm observed for particles transferring through entrainment or entrapment.